help me please! will mark brainliest for the correct answer
![help me please will mark brainliest for the correct answer class=](https://us-static.z-dn.net/files/de7/5aee1d82b51ed785e06ea9c0737d49b0.png)
Answer:
see explanation
Step-by-step explanation:
Using the rules of exponents
[tex]a^{m}[/tex] × [tex]a^{n}[/tex] ⇔ [tex]a^{(m+n)}[/tex]
[tex](a^m)^{n}[/tex] = [tex]a^{mn}[/tex]
[tex]a^{-m}[/tex] ⇔ [tex]\frac{1}{a^{m} }[/tex]
Thus
[tex]4^{3x-2}[/tex]
= [tex]4^{3x}[/tex] × [tex]4^{-2}[/tex]
= [tex](4^3)^{x}[/tex] × [tex]4^{-2}[/tex]
= [tex]64^{x}[/tex] × [tex]\frac{1}{4^2}[/tex]
= [tex]\frac{64^{x} }{16}[/tex] ← as required